Use of automated in-line capable magnetic stray field measurement method for monitoring the value chain quality of magnetic circuits - Brela, Matthäus; Heyder, Andreas; Dietlein, Fabian; Markert, Johannes; Franke, Jörg; Hauenstein, R.; Wagner, R. (2014 International Symposium on Power Electronics, Electrical Drives, Automation and Motion, SPEEDAM 2014, 2014)
Common defects in electromagnetic actuators due to the manufacturing process are heterogeneous magnetic properties of the materials, cracks and defects in the magnetic materials and parasitic air gaps in and directly around the magnetic circuit. In most cases the error cause can be found in the value chain and is caused by material handling, assembling tolerances, environmental influences, etc. Considering the high global cost pressure, test systems must be adapted to the increasing complexity of the components in order to be able to detect defects completely in-situ and have smallest possible amortization period. For these requirements the novel and nondestructive measurement system is suitable to monitor and assure quality of magnetic actuators within the manufacturing process. The measuring principle is the characterization of electromagnetic actuators according to the detection of magnetic stray fields outside the magnetic circuit and the magnetic useful field inside the actuator that can be quantified by magnetic sensors. The intensity of the magnetic stray fields depends on the magnetic flux density and flux distribution in the magnetic circuit. Permeability variations for example caused by air gaps or internal stresses influence the flux distribution. In most cases they are caused by process parameter variations of the manufacturing and assembling. With the developed method this influences can be detected in an early stage of the manufacturing process automatically and in-line. This can lead to more competitiveness and long-term viability of the location. © 2014 IEEE.
CRIS-Team Scopus Importer:2023-03-07